VR Teaching Media Creation Training as an Effort to Improve Pedagogical Competence in the Implementation of the Independent Curriculum : Pelatihan Pembuatan Media Ajar VR Sebagai Upaya Peningkatan Kompetensi Pedagogik Dalam Implementasi Kurikulum Merdeka - Sakdiah, Halimatus; Ginting, Fajrul Wahdi; Fatwa, Islami (Universitas Lancang Kuning, 2025)
Training in creating Virtual Reality (VR)-based teaching media aims to improve teachers' pedagogical competence in implementing the Independent Curriculum. The use of VR technology in teaching media provides an interactive and immersive learning experience, thus encouraging students to be more active and creative. This activity program involves the Lhokseumawe City Teacher Communication Forum (FKGPL), namely 30 teacher leaders as participants. The implementation of the activity uses a training method in creating VR media for 2 days, namely September 11-12, 2024 in the hall of the Lhokseumawe City Office branch. Participants are able to produce one VR media according to the field of study taught by each participant. The results of the activity, although they have difficulties and require time in the process, the participants managed to compile VR media according to their field of study and improve the participants' pedagogical abilities by 30%. This training program is a basic skill for participants in virtualizing teaching materials, so that they can design virtual-based learning.